A Risk Score to Detect Subclinical Rheumatoid Arthritis–Associated Interstitial Lung Disease. Issue 11 (5th October 2022) - Juge, Pierre‐Antoine; Granger, Benjamin; Debray, Marie‐Pierre; Ebstein, Esther; Louis‐Sidney, Fabienne; Kedra, Joanna; Doyle, Tracy J.; Borie, Raphaël; Constantin, Arnaud; Combe, Bernard; Flipo, René‐Marc; Mariette, Xavier; et al.
Abstract : Objective: Patients at high risk of rheumatoid arthritis–associated interstitial lung disease (RA‐ILD) would benefit from being identified before the onset of respiratory symptoms; this can be done by screening patients with the use of chest high‐resolution computed tomography (HRCT). Our objective was to develop and validate a risk score for patients who have subclinical RA‐ILD. Methods: Our study included a discovery population and a replication population from 2 prospective RA cohorts (ESPOIR and TRANSLATE2, respectively) without pulmonary symptoms who had received chest HRCT scans. All patients were genotyped for MUC5B rs35705950. After multiple logistic regression, a risk score based on independent risk factors for subclinical RA‐ILD was developed in the discovery population and tested for validation in the replication population. Results: The discovery population included 163 patients with RA, and the replication population included 89 patients with RA. The prevalence of subclinical RA‐ILD was 19.0% and 16.9%, respectively. In the discovery population, independent risk factors for subclinical RA‐ILD were presence of the MUC5B rs35705950 T allele (odds ratio [OR] 3.74 [95% confidence interval (95% CI) 1.37, 10.39]), male sex (OR 3.93 [95% CI 1.40, 11.39]), older age at RA onset (for each year, OR 1.10 [95% CI 1.04, 1.16]), and increased mean Disease Activity Score in 28 joints using the erythrocyte sedimentation rate (for each unit, OR 2.03 [95% CI 1.24, 3.42]). We developed and validated a derived risk score with receiver operating characteristic areas under the curve of 0.82 (95% CI 0.70–0.94) for the discovery population and 0.78 (95% CI 0.65–0.92) for the replication population. Excluding MUC5B rs35705950 from the model provided a lower goodness of fit (likelihood ratio test, P  = 0.01). Conclusion: We developed and validated a risk score that could help identify patients at high risk of subclinical RA‐ILD. Our findings support an important contribution of MUC5B rs35705950 to subclinical RA‐ILD risk.